2016
DOI: 10.1101/038505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary games of multiplayer cooperation on graphs

Abstract: There has been much interest in studying evolutionary games in structured populations, often modelled as graphs. However, most analytical results so far have only been obtained for two-player or linear games, while the study of more complex multiplayer games has been usually tackled by computer simulations. Here we investigate evolutionary multiplayer games on graphs updated with a Moran death-Birth process. For cycles, we obtain an exact analytical condition for cooperation to be favored by natural selection,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 72 publications
0
30
0
1
Order By: Relevance
“…the linear approximation at r = 1), according to Eqs. (4), (8), and (13). (D) In the n → ∞ limit, fixation probability is given by Eq.…”
Section: Fanmentioning
confidence: 99%
“…the linear approximation at r = 1), according to Eqs. (4), (8), and (13). (D) In the n → ∞ limit, fixation probability is given by Eq.…”
Section: Fanmentioning
confidence: 99%
“…Our study revealed a perhaps counterintuitive result, namely, that increasing spatial structure can be detrimental to prosocial rewarding. While spatial structure generally favors the evolution of cooperation (Ohtsuki et al, 2006;Lehmann et al, 2007;Perc et al, 2013;Mullon and Lehmann, 2014;Débarre et al, 2014;Peña et al, 2016b), it can sometimes oppose it Van Cleve and Lehmann, 2013;Peña et al, 2016a). In our case, spatial structure can oppose selection because the indirect gains from switching from antisocial to prosocial rewarding can be negative.…”
Section: Discussionmentioning
confidence: 62%
“…For example, Hauert and Doebeli 63 found that, when social interactions are modelled as a two-player snowdrift game between pure strategists under strong selection, well-mixed populations lead to higher levels of cooperation than square lattices. Peña et al 64 studied a multiplayer version of this game, but assuming weak selection and a death-birth Moran process, and found similar results. In our case, spatial structure can oppose prosocial rewarding because the indirect gains from switching from antisocial to prosocial rewarding can be negative.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations